Geology and origins of the Mike Lake (Skarn Ridge) gold-copper skarn deposit, Yukon Territory, Canada - Mrozek, Stephanie Anne (2012)
Thesis (M.S.) University of Alaska Fairbanks, 2012 The Mike Lake (Skarn Ridge) deposit has an elemental suite of Cu-Au-Bi-As-Sn and a mineralogy dominated by scapolite, clinopyroxene, and pyrrhotite, with lesser garnet and Fe-axinite (a Ca-borosilicate). This study is the first published description of the deposit. The deposit was studied with techniques including drill core logging and detailed surface mapping (1:5,000 scale), combined with petrographic examination of polished thin sections, X-ray fluorescence and X-ray diffraction analyses, electron microprobe analysis of major minerals, and ⁴⁰Ar/³⁹Ar dating. Ore mineralization styles include vein-controlled, disseminated, and net-textured replacements of clinopyroxene and calcite by electrum, chalcopyrite, pyrrhotite, and arsenopyrite, with variable native bismuth and bismuth tellurides. A strong Au:Bi correlation (R² = 0.74) indicates the two elements were transported and deposited together; however a poor Au:Cu correlation (R² = 0.23) suggests different mineralization events or different modes of Au-Cu transport. The virtual absence of retrograde alteration provides an ideal opportunity to examine metal- and silicate-zoning patterns apparently associated with prograde alteration. Using the ⁴⁰Ar/³⁹Ar dating method, I have determined that the adjacent Mike Lake pluton is younger than the skarn, and hence, genetically unrelated. Through analysis of samples from surface and 72 drill holes, I show systematic zoning in skarn mineralogy and mineral compositions suggesting deposit derivation from an unknown pluton to the southeast at depth.